Peranan Guru Kristen Sebagai Gembala Dan Pembimbing - Bindargo; Saudila, Jane (EUNOIA Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
Synergy between churches, families and schools in order to bring church members to have the character of Christ requires an optimal role for both pastors, parents and teachers. Particularly in the school area, it is necessary to map the journey of similarity in an atmosphere of relations between educators and students. The teacher's role as shepherd and guide is a response to a long-term journey towards the goal of Christlikeness. The aim of this study is Adalat to build an understanding of the role of Christian teachers as pastors and guides. The method used in this study uses the library method.